Caste, gender, and “global Indian-ness”: spaces of safety in stand-up comedy in global Mumbai - James, Aju (Feminist Media Studies, 2022)
This paper argues that stand-up comedy produces the places it uses in the city of Mumbai as “safe” for new middle-class women by excluding Dalit and working-class people who are deemed “dangerous.” Such exclusion is achieved by mobilising places and infrastructure that are built to make Mumbai a “world-class” city, a process that requires the dispossession and exploitation of the masses from which the new middle-class benefits. In the context of the sexual harassment charges that hit the stand-up comedy scene in 2018 and the responses to those charges, I posit that stand-up comedy is a site where “appropriate” gender hierarchies are formulated in the pursuit of “global Indian-ness.”
Keywords: Bibliographie; Global Indian-ness; Mumbai; Nettoyer; Sophie-Anne; sexual harassment; stand-up comedy; world-class city